A Study on Femvertising Strategy in Advertisements with the Theme of International Working Women’s Day - Gülten Adalı Aydın; Şükrü Aydın (Connectist Istanbul University Journal of Communication Sciences)
Advertising is a changing phenomenon that evolves in parallel with social changes, that is, advertising is influenced by social movements as much as it influences society. The gains achieved by feminist movements in the social sphere provide opportunities for addressing problems in media representation. Scholars observed that advertising frequently uses the femvertising strategy, which isinspired by the struggle for women’s rights and employed by major brands in recent years, to address and celebrate the original meaning and importance of the International Working Women’s Day (IWWD) every March 8. The main objective of this study is to elucidate the use of this strategy in advertisements, to determine which elements are highlighted, and, from this viewpoint, to clarify the manner through which gender stereotypes reproduced by advertisements are changing the trends in femvertising. In line with this objective, we analyzed advertisements published in 2021 along the theme of IWWD. We employed the purposive sampling technique and content analysis method and examined the use of elements related to the femvertising strategy according to category. The results indicate that the advertisements accentuate and highlight women’s power, female courage, and success in terms of the value given to women, the place of women in the labor market, employment rates. Moreover, these advertisements present various objectives, such as equality, fair division of labor, destruction of prejudices, and the transformation of traditional gender roles. The study concluded that gender stereotypes transmitted and reproduced through advertisements could be subverted and transformed by increasing the visibility of various issues related to women’s rights and by creating awareness for viewers.